1998
DOI: 10.2307/3870662
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Cell-Specific Inositol Metabolism and Transport in Plant Salinity Tolerance

Abstract: myo-Inositol and its derivatives are commonly studied with respect to cell signaling and membrane biogenesis, but they also participate in responses to salinity in animals and plants. In this study, we focused on L-myo-inositol 1-phosphate synthase (INPS), which commits carbon to de novo synthesis, and myo-inositol O-methyltransferase (IMT), which uses myo-inositol for stress-induced accumulation of a methylinositol, D-ononitol. The Imt and Inps promoters are transcriptionally controlled. We determined that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
44
0
2

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 18 publications
6
44
0
2
Order By: Relevance
“…8). Increased synthesis of inositol and its transport has been shown previously to play a major role in sequestration of sodium ions and maintenance of photosynthetic competence during salt stress (42,46). A protective role for inositol in maintaining the photosynthetic efficiency of the plants, as demonstrated previously for other osmolytes like glycine-betaine or proline (43,(47)(48), may also be inferred from such results.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…8). Increased synthesis of inositol and its transport has been shown previously to play a major role in sequestration of sodium ions and maintenance of photosynthetic competence during salt stress (42,46). A protective role for inositol in maintaining the photosynthetic efficiency of the plants, as demonstrated previously for other osmolytes like glycine-betaine or proline (43,(47)(48), may also be inferred from such results.…”
Section: Discussionsupporting
confidence: 51%
“…Regulation of inositol pathway in relation to salt stress has also been studied earlier (21,42). In a facultative halophyte-like Mesembryamthemum crystallinum, a coordinate transcriptional induction of INO1 and the inositol methyltransferase (IMT) gene(s) under salt environment for production of both inositol and its methylated derivative, pinitol has been documented (49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In leaves of unstressed soybean (Glycine max), for example, concentrations of pinitol (3-O-methyl-chiroinositol) can be 2-fold higher than the combined concentrations of Suc, all monosaccharides, and myoinositol (Smith and Phillips, 1982;Streeter et al, 2001). This already high concentration is further increased in droughtstressed plants, underlining the important role of unmethylated and methylated inositols as osmoprotectants (Thomas and Bohnert, 1993;Sheveleva et al, 1997;Nelson et al, 1998;Hasegawa et al, 2000;Streeter et al, 2001;Murakeö zy et al, 2003).…”
mentioning
confidence: 97%
“…Among the selected enzymes, Myo-inositol-1-phosphate synthase (INPS, BE644574) is the key enzyme of Myo-inositol (Ins) biosynthesis. It has been confirmed that INPS regulates the pathway of Ins biosynthesis (Nelson et al, 1998), which is a specific pathway in salt tolerance in the common ice plant (Vernon and Bohnert, 1992), and its expression can be feedback inhibited by myo-inositol. In higher plants, betaine is synthesized by oxidation of choline: cholinebetaine aldehyde-betaine.…”
Section: Introductionmentioning
confidence: 92%